2006
DOI: 10.1186/1476-069x-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial lipopolysaccharides and human health – a review

Abstract: Cyanobacterial lipopolysaccharide/s (LPS) are frequently cited in the cyanobacteria literature as toxins responsible for a variety of heath effects in humans, from skin rashes to gastrointestinal, respiratory and allergic reactions. The attribution of toxic properties to cyanobacterial LPS dates from the 1970s, when it was thought that lipid A, the toxic moiety of LPS, was structurally and functionally conserved across all Gram-negative bacteria. However, more recent research has shown that this is not the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 234 publications
(269 reference statements)
0
132
0
2
Order By: Relevance
“…This compound is considered to be produced by all cyanobacteria and is a structural constituent of the outer layers of the cell wall (Metcalf and Codd, 2004). Cyanobacterial LPS is attributed with a range of pathological effects in humans, from cutaneous signs and symptoms, gastrointestinal illness, respiratory disease, allergy, headache and fever (Stewart et al, 2006). On aquatic community, studies demonstrate that cyanobacterial LPS stimulate drinking in fish, the increased volume of water in the gut potentially increases the opportunity for uptake of toxins (including MC) from the water and promotes osmoregulatory imbalance on rainbow trout (Best et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This compound is considered to be produced by all cyanobacteria and is a structural constituent of the outer layers of the cell wall (Metcalf and Codd, 2004). Cyanobacterial LPS is attributed with a range of pathological effects in humans, from cutaneous signs and symptoms, gastrointestinal illness, respiratory disease, allergy, headache and fever (Stewart et al, 2006). On aquatic community, studies demonstrate that cyanobacterial LPS stimulate drinking in fish, the increased volume of water in the gut potentially increases the opportunity for uptake of toxins (including MC) from the water and promotes osmoregulatory imbalance on rainbow trout (Best et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the LPS of cyanobacteria may cause or contribute to human illness, particularly in causing epidermal allergic reactions. However, there is little evidence in the scientific literature that skin contact with the LPS of cyanobacteria causes a skin rash [53,54]. Rather, it may be that skin rashes after cyanoHAB exposure are caused by one of hundreds of other bioactive metabolites produced by cyanobacteria.…”
Section: Dermatoxinsmentioning
confidence: 97%
“…Dans ces milieux aquatiques, les cyanobactéries sont souvent l'origine d'intoxications mortelles de troupeaux d'animaux domestiques ou sauvages, de poissons, d'oiseaux et même de l'Homme. En effet, les cyanobactéries sont capables de produire des substances possédant des propriétés toxiques à savoir l'hépatotoxicité, la neurotoxicité, la dermatotoxicité et les syndromes gastro-intestinaux [2][3][4]. En revanche, plusieurs travaux ont montré que les cyanobactéries constituent une nouvelle source de composés bioactifs [5][6][7].…”
Section: Introductionunclassified